Patterns of Objective and Subjective Burden of Informal Caregivers in Multiple Sclerosis - E. Bayen; C. Papeix; P. Pradat-Diehl; C. Lubetzki; M. E. Joël (Behavioural Neurology)
Background. Home care for patients with Multiple Sclerosis (MS) relies largely on informal caregivers (ICs). Methods. We assessed ICs objective burden (Resource Utilization in Dementia measuring informal care time (ICT)) and ICs subjective burden (Zarit Burden Inventory (ZBI)). Results. ICs (N=99) were spouses (70%), mean age 52 years, assisting disabled patients with a mean EDSS (Expanded Disability Status Scale) of 5.5, with executive dysfunction (mean DEX (Dysexecutive questionnaire) of 25) and a duration of MS ranging from 1 to 44 years. Objective burden was high (mean ICT = 6.5 hours/day), mostly consisting of supervision time. Subjective burden was moderate (mean ZBI = 27.3). Multivariate analyses showed that both burdens were positively correlated with higher levels of EDSS and DEX, whereas coresidency and IC’s female gender correlated with objective burden only and IC’s poor mental health status with subjective burden only. When considering MS aggressiveness, it appeared that both burdens were not correlated with a higher duration of MS but rather increased for patients with severe and early dysexecutive function and for patients classified as fast progressors according to the Multiple Sclerosis Severity Score. Conclusion. Evaluation of MS disability course and IC’s personal situation is crucial to understand the burden process and to implement adequate interventions in MS.